2010
DOI: 10.4321/s0004-06142010000200007
|View full text |Cite
|
Sign up to set email alerts
|

Expresión de metaloproteasa de matriz 9 en el cáncer de próstata: Experiencia preliminar

Abstract: Resumen.-OBJETIVO: Estudiar la validez de la metaloproteasa 9

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…González Rodrigues et al [ 14 ] found unsatisfactory results when serum MMP-9 was determined by ELISA in 100 patients with indication for prostate biopsy (prospective cohort study). Of these, 32 were diagnosed with PCa with 52% classified with Gleason greater than or equal to 7.…”
Section: Introductionmentioning
confidence: 99%
“…González Rodrigues et al [ 14 ] found unsatisfactory results when serum MMP-9 was determined by ELISA in 100 patients with indication for prostate biopsy (prospective cohort study). Of these, 32 were diagnosed with PCa with 52% classified with Gleason greater than or equal to 7.…”
Section: Introductionmentioning
confidence: 99%